The effect of pharmacists on ward rounds measured by the STOPP/START tool in a specialized geriatric unit. (16th December 2016) - Mulvogue, K.; Roberts, J. A.; Coombes, I.; Cottrell, N.; Kanagarajah, S.; Smith, A.
Abstract : Summary: What is known and objective: The STOPP/START tool has been validated to assess elderly patients for potentially inappropriate prescribing. This study aimed to assess the effect of inclusion of a pharmacist on a physician‐led ward round on potentially inappropriate prescribing in hospitalized elderly patients. Methods: This was an observational study of prescribing for patients using the STOPP/START tool at three points during hospital stay; admission to hospital, on transfer to the specialized geriatric unit and on discharge from hospital. Data were collected over 4 months pre‐ and post‐introduction of a pharmacist to a physician‐led ward round. Demographic and clinical data, including total number of medications and STOPP/START criteria met, were collected. The mean number of STOPP/START criteria at each time‐point was compared for pre‐ and post‐introduction of a pharmacist using a Mann–Whitney U ‐test. The mean number of criteria for each time‐point within each group was compared using a paired Student's t ‐test. Results and discussion: The demographic characteristics of the participants in the pre‐ and post‐intervention groups were similar. The post‐intervention group had numerically less STOPP/START criteria, mean 1·18 (1·37) compared to the pre‐intervention group 1·50 (1·41), P = 0·07 at discharge. The pre‐intervention group had no significant change in the criteria from admission 1·78 (1·57) to geriatric unit transfer 1·72 (1·54) ( P = 0·37); however, there was a significant decrease from geriatric unit transfer 1·72 (1·54) to discharge 1·50 (1·41) ( P = 0·02). The post‐intervention group had a significant decrease from hospital admission 2·30 (1·91) to geriatric unit transfer 1·59 (1·60) ( P < 0·01) and again to discharge 1·18 (1·37) ( P < 0·01). What is new and conclusion: Pharmacist participation on the ward round in a specialized geriatric unit resulted in a numerical improvement in prescribing quality as measured by the STOPP/START tool. Abstract : This study used STOPP/START to assess prescribing throughout a hospital stay for patients over 65 years whose stay included an admission in a specialized geriatric unit using two different models of pharmacist care. The mean number of STOPP/START identified per patient decreased after an admission in the geriatric unit for both groups and this decrease was larger in the group where the pharmacist participated on the physician‐led ward round.